2016
DOI: 10.1177/0004563216672248
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid and antioangiogenic activity in females with recurrent miscarriage and antiphospholipid syndrome

Abstract: Ethical approval: The study was approved by the Bioethics Comitee of Facultad de Ciencias Bioquímicas y Farmacéuticas (Universidad Nacional de Rosario). Res Nº 076/2008. All participants signed the corresponding informed consent. Guarantor: SMMA Contributorship: HFP performed most assays and analysis of results, and wrote the paper. EP and CB performed some assays and collaborated in the analysis of results. JM performed patients selection for the study and aided in medical matters. MB, MJS and SMD performed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These factors eventually lead to abortion, placental disease, fetal growth restriction, and other adverse pregnancy outcomes. [ 10 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…These factors eventually lead to abortion, placental disease, fetal growth restriction, and other adverse pregnancy outcomes. [ 10 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…The condition is associated with parental chromosomal anomalies, uterine abnormalities, endocrine factors, thrombophilia, cervical insufficiency and immunological disorders [1][2][3][4][5][6]. Of the various RM-related immunological disorders, antiphospholipid antibody syndrome (APS) is the most common [7,8]. Previous studies have revealed that platelet-derived microparticles (PMPs), small vesicles that arise from platelets, play a crucial role in mediating immune disorders [9,10].…”
Section: Introductionmentioning
confidence: 99%